Association between occupational sedentary behavior and metabolic syndrome and related diseases in males: A cross-sectional study - Zhonglan Yin; Shaofan Weng; Dafeng Lin; Wei Zhou; Naixing Zhang (PLoS ONE, 2026)
Background Prolonged occupational sedentary behavior has become a prevalent norm in workplaces, posing significant health risks. However, there is a scarcity of studies on the association between occupational sedentary behavior with metabolic syndrome (MetS) and related diseases among workers. Methods From June 2023 to November 2024, 2,055 male bus drivers (occupational sedentary group) and sanitation workers (non-sedentary group) were enrolled by cluster sampling. Questionnaire surveys and clinical examinations were collected retrospectively. MetS was diagnosed according to the Guidelines for the Prevention and Treatment of Diabetes Mellitus in China (2024 Edition) . Logistic regressions and subgroup analyses were conducted to determine the associations between occupational sedentary behavior with MetS and related diseases. Results The occupational sedentary group (1,158 participants) had higher prevalence of metabolic syndrome (24.61% vs. 22.63%), hypertriglyceridemia (51.81% vs. 36.34%), hypoalphalipoproteinemia (12.35% vs. 9.03%), and central obesity (36.62% vs. 29.43%), compared to the non-sedentary group (897 participants). In the logistic regression model, no significant correlations were observed between occupational sedentary behavior and MetS ( P > 0.05). Compared with non-sedentary group, the sedentary group showed an increased risks of hypertriglyceridemia [OR (95% CI) = 1.77 (1.41, 2.22)], hypoalphalipoproteinemia [OR (95% CI) = 1.44 (1.01, 2.06)], and central obesity [OR (95% CI) = 1.37 (1.09, 1.74)]. Subgroup logistic regression analysis showed that among subjects aged >55 years, the associations between occupational sedentary behavior with hypertriglyceridemia and central obesity were significantly stronger (all P for interaction < 0.05). Conclusion Occupational sedentary behavior in males is associated with higher prevalence of hypertriglyceridemia, hypoalphalipoproteinemia, and central obesity. Interventions to reduce sedentary behavior are needed to mitigate these risks, such as lifestyle, and organizational management strategies.